KESIAPAN SATUAN KERJA PENGGUNA ANGGARAN PENDAPATAN DAN BELANJA NEGARA DALAM RANGKA E-BUDGETING YANG DICANANGKAN PEMERINTAH PUSAT (STUDI KASUS BPK RI PERWAKILAN PROVINSI DAERAH ISTIMEWA YOGYAKARTA) - , Haryanto, Prof. (Emr). Adhi Susanto, M. Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In state finance management, use of Information and Communication Technology (ICT) is realized by e-budgeting. In charge of e-budgeting, Ministry of Finance (MoF) launched State Treasury and Budget System (SPAN). SPAN is targeted fully implemented in 2013. Because e-budgeting is focused on the use of ITC in budgeting process, it needs e-budgeting readiness and acceptance from state budget spending unit. The research aims to measure e-budgeting readiness level in The Audit Board of The Republic of Indonesia (BPK RI) Yogyakarta Special Region (DIY) Province Representative as well as analyze the effect of technology readiness on technology acceptance in the e-budgeting context. The models used is Technology Readiness Index (TRI) dan Unified Theory of Acceptance and Usage of Technology (UTAUT). The data was collected by questionnaires and interviews. Data obtained were analyzed using Structural Equation Modeling (SEM) with help of software SmartPLS version 2.0 M3. Result indicated that BPK RI DIY Province Representative employeesâ readiness level on e-budgeting is pioneer. Data analysis also showed that dimension optimism effect on performance expectancy dan dimensions innovativeness, discomfort, dan insecurity effect on effort expectancy. Ebudgeting acceptance in BPK RI DIY Province Representative is not affected by employeesâ e-budgeting readiness.